THE CURRENT STATE OF AUTOMATIC GEARBOXES - Gheorghe GÎLCĂ (Fiabilitate şi Durabilitate)
The paper presents the working principle of an automatic gearbox. It also describes the main gear change programs as well as the memorized maps, the latter showing the driving regime depending on the set gear.